Examining the Effects of Oil Revenue, Exchange Rate, and Fiscal Shocks on Military Expenditures in Iran: DSGE approach - Farideh Khodadadi; Seyyed Reza Nakhli (اقتصاد باثبات)
The aim of this research is to investigate the effects of fiscal shock, exchange rate shock, and trade shock on military expenditures in Iran a major oil-producing country in the Middle East. To achieve this goal, a New Keynesian Dynamic Stochastic General Equilibrium (DSGE) model was designed, incorporating the realities of the Iranian economy in the macroeconomic variables and calibration of the parameters. The model was then used to analyze the effects of various shocks. After determining the input values of the model and estimating the parameters using Bayesian estimation methods with seasonal data from the Iranian economy over the period 1991-2023, the simulation results of the model variables indicate the model's validity in describing the fluctuations of the Iranian economy. The results of the model show that oil and exchange rate shocks have a positive effect on military expenditures. However, fiscal shocks initially have a negative impact on military expenditures, but over time, that shock exerts a different effect on the trend of expenditures. Except for the exchange rate and oil shocks, where the return to a stable state of military expenditure variables is prolonged and the effects of the shock dissipate slowly, the tax shock returns to its stable state after a short period. In other words, the effects of these two shocks (oil and exchange rate shocks) differ slightly from the fiscal shock in both amplitude and duration of fluctuations. This underscores the importance of oil and the value of the national currency for the Iranian economy.